Cellullar insights into cerebral cortical development: focusing on the locomotion mode of neuronal migration - Kawauchi, Takeshi (Frontiers in Cellular Neuroscience, 2015)
The mammalian brain consists of numerous compartments that are closely connected with each other via neural networks, comprising the basis of higher order brain functions. The highly specialized structure originates from simple pseudostratified neuroepithelium-derived neural progenitors located near the ventricle. A long journey by neurons from the ventricular side is essential for the formation of a sophisticated brain structure, including a mammalian-specific six-layered cerebral cortex. Neuronal migration consists of several contiguous steps, but the locomotion mode comprises a large part of the migration. The locomoting neurons exhibit unique features; a radial glial fiber-dependent migration requiring the endocytic recycling of N-cadherin and a neuron-specific migration mode with dilation/swelling formation that requires the actin and microtubule organization possibly regulated by cyclin-dependent kinase 5 (Cdk5), Dcx, p27kip1, Rac1 and POSH. Here I will introduce the roles of various cellular events, such as cytoskeletal organization, cell adhesion and membrane trafficking, in the regulation of the neuronal migration, with particular focus on the locomotion mode.